PEMBATALAN KEWENANGAN KOMISI YUDISIAL DALAM REKRUTMEN HAKIM DIKAITKAN DENGAN KONSEP INDEPENDENSI HAKIM - Zaki Ulya (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractRelationship problems Judicial Commission and the Supreme Court re-strained due to the addition of authority in the appointment of judges first instance courts. It is set in the third package of legislation, namely Law No. 49 of 2009, Law No. 50 of 2009 and Law No. 51 of 2009. The three laws are carried out judicial review to the Constitutional Court by Decision No. 43/ PUU-XIII/ 2015. The Constitutional Court stated that the expansion of the authority of the Judicial Commission against the constitution and interfere with the independence of judges as an independent institution. The purpose of this paper is to examine the decision is linked to the independence of judges and the impact of such decision to the authority of the Judicial Commission.IntisariDilematika hubungan Komisi Yudisial dan Mahkamah Agung kembali renggang akibat adanya penambahan wewenang dalam pengangkatan hakim peradilan tingkat pertama. Hal tersebut diatur dalam ketiga paket undang-undang yaitu Undang-Undang Nomor 49 Tahun 2009, Undang-Undang Nomor 50 Tahun 2009, dan Undang-Undang Nomor 51 Tahun 2009. Ketiga undang-undang tersebut dilakukan yudicial review ke Mahkamah Konstitusi dengan Putusan Nomor 43/PUU-XIII/2015. Mahkamah Konstitusi menyatakan bahwa perluasan wewenang Komisi Yudisial bertentangan dengan konstitusi dan mengganggu independensi hakim sebagai lembaga mandiri. Tujuan penulisan ini adalah untuk mengkaji putusan tersebut dikaitkan dengan independensi hakim serta dampak dari putusan tersebut terhadap wewenang Komisi Yudisial.